TINGKAT PENERIMAAN KONSUMEN TERHADAP TEH DAUN BINAHONG (Anredera cordifolia (Ten.) Steenis) PADA VARIASI SUHU DAN WAKTU PENYEDUHAN - Langi, Tineke; Haras, Moh Syafat; Assa, Jan R. (Jurnal Teknologi Pertanian (Agricultural Technology Journal, 2018)
Antioxidants are compounds that can counteract the negativeeffects of free radicals in the body. Binahong leaves (Anredera cordifolia(Ten.) Steenis) contain steroids, alkaloids, flavonoids, saponins,polyphenols and tannins which can potentially have antioxidant capacity.Binahong leaf tea is an herbal tea produced from fresh binahong leaveswhich has antioxidant content. The purpose of this study was to determinethe antioxidant activity at the varied immertion temperature. This studyused a descriptive method at variations in immertion temperatures of60â°C, 80â°C and 100â°C for 5 minutes. Antioxidant activity test was carriedout on DPPH, total flavonoids and total Phenol. The highest DPPHscavenging activity obtained at 100â°C was 62.15% with total flavonoidsand total phenolic were 120 mg / 100g and 327.75 mg / 100g, respectively.Keywords: Binahong Leaf Tea, Antioxidant Activity